고려 홍삼 투여가 지속적 내리막 달리기 후 CK, GOT, peak torque 및 ROM에 미치는 영향 - 김형돈; Hyung Don Kim; 노호성; Ho Sung Nho; 길재호; Jae Ho Khil (Ch'eyuk kwahak yŏn'gu, 2004)
스프린트나 지속적 하향달리기와 같은 고강도의 신장성 운동은 골격근에서 발견되는 혈장 효소의 상당한 변화를 초래하며 또한 근 통증의 발달과 근력의 저하를 가져오는 것으로 알려져 있다. 신장성 운동에 의한 근 손상을 최소화하기 위하여 여러 형태의 처치들이 처방되고 있으며, 본 연구에서는 고려 홍삼이 고강도의 downhill 달리기 후 회복과정에서 미칠 수 있는 근 손상에 대한 보호효과를 확인하는 것이 목적이다. 24명의 대상자들은 이중 맹검법에 의해 무선으로 실험집단(n=12) 또는 위약집단(n=12)으로 나뉘어졌다. 각각의 집단은 고려 홍삼 추출분말 또는 위약(옥수수전분) 캡슐(50mg kg-1 day-1)을 3주간 복용하였으며, 2 주 복용 후 -10% 경사도의 트레드밀에서 70% VO2max의 강도로 45분간 지속적인 달리기를 실시하였다. CK, GOT, ROM과 등척성 및 등속성 피크토크는 downhill 달리기 전, 1일, 2일, 1주일 후에 측정하였다. Downhill 달리기 1주일 전에 downhill 달리기의 운동 강도를 설정하기 위하여 VO2max 검사를 실시하였다. 시기에 따른 집단간의 차이는 repeated measure two way ANCOVA를 통하여, 집단 내 시기에 따른 변화는 one way repeated measure ANOVA를 통하여 분석하였으며 유의수준은 0.05로 설정하였다. 실험집단의 plasma CK, 등척성 피크 토크 와 ROM은 위약집단에 비해 회복기간 중 유의하게 회복되었으며(p<.05) 또한 유의한 (p<.05)상호작용 효과가 발견되었다. 또한, 실험집단은 달리기 후 CK에서 유의하게 증가하였으며. 등척성 피크 토크 및 ROM은 유의하게 감소하였으나 1주일 후에는 downhill 달리기 이전의 정상 상태로 회복하였다. 위약집단 역시 downhill 달리기 후 유의하게 감소하였으나 회복 상태는 상대적으로 지연되었다. 이 같은 결과로 미루어볼 때 고려 홍삼은 근 손상 후 회복과정에서 보호적인 효과를 발휘하였으며, 근 손상 회복을 위한 효과적인 처치 방법 중의 하나가 될 수 있는 것으로 믿어진다. Strenuous eccentric exercise such as downhill running induces remarkable changes of plasma enzyme found in skeletal muscle, and also causes the development of soreness and the loss in muscle strength. The Korean red ginseng was investigated to determine its protective effects during the recovery period after strenuous downhill running. Twenty four male college students participated in the double-blind, placebo-controlled study. The subjects were randomly assigned to either an experimental group (n=12) or placebo group (n=12). Each group received either crude extract powder of Korean red ginseng or placebo (corn starch) for 14 days before and 7 days after a -10% downhill 45-min treadmill run at 70% VO2max (50mg kg-1 day-1). CK, GOT, ROM and maximal isometric and isokinetic force were measured before and 1, 2, 7 days after downhill running. VO2max was also determined on the treadmill 7 days before downhill running for calculation of relative intensity of downhill running. Body composition was measured by electrical impedance method. Differences of groups were analysed using repeated measure two way ANCOVA. One way repeated measure ANOVA was also used to determine difference within each group. Alpha level was set at 0.05. Plasma CK, isometric peak torque, and ROM of experimental group significantly changed during the period of rehabilitation after downhill running (p＜.05). Significant differences were also observed over time between groups (p＜.05) in CK, isometric peak torque, and ROM. The experimental group dropped in maximal isometric force and ROM from pre-exercise value after downhill running and then significantly regain a strength and ROM (p＜.05). It is concluded that Korean red ginseng is very effective to reduce muscle damages and improve recovery rate during the course of rehabilitation.